Estymatory kalibracyjne kwantyli rozkładu dochodów i wydatków gospodarstw domowych w BBGD - Klimanek, Tomasz; Paradysz, Jan; Szymkowiak, Marcin (The Calibration Estimators of Quantiles of Households' Incomes and Expenditures Distribution in Household Budget Survey, 2009)
The main objective of the paper is to present the calibration estimators used in Household Budget Survey (HBS) which are essential as far as methodology in surveys with nonresponse is concerned. HBS is the survey in which besides the nonresponse one has to deal with the problem of highly skewed distributions. The article presents selected calibration estimators of quantiles according to the idea of calibration proposed by J.-C. Deville, C.-E. Särndal and S. Lundström and developed by T. Harms and P. Duchesne. The theoretical foundations are accompanied by the empirical attempt to apply the discussed estimators in HBS. Moreover, the comparison between calibration estimators of quantiles and classical ones, well-known in literature, is made. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 79-87